Odpowiedzi

  • Użytkownik Zadane
2009-10-25T14:02:37+01:00
A=(-3, 0)
B=<-1,4)
AuB=(-3,4)
AnB=<-1,0)
A\B=(-3,-1)
B\A=<0,4)

A=<-4,2)
B=<-1/2, 3)
AuB=<-4,3)
AnB=<-1/2,2)
A\B=<-4,-1/2)
B\A=<2,3)

A=(-∞, 2>
B=<0,2)
AuB=A=(-∞, 2>
AnB=B=<0,2)
A\B=(-∞, 0)
B\A=zbiór pusty

A=<-1,2>
B=<2, +∞)
AuB=<-1,+∞)
AnB={2}
A\B=<-1,2)
B\A=(2,+∞)
1 5 1
2009-10-25T14:05:04+01:00
A=(-3, 0)
B=<-1,4)
AuB=(-3,4)
AnB=<-1,0)
A\B=(-3,-1)
B\A=<0,4)

A=<-4,2)
B=<-1/2, 3)
AuB=<-4,3)
AnB=<-1/2,2)
A\B=<-4,-1/2)
B\A=<2,3)

A=(-∞, 2>
B=<0,2)
AuB=A=(-∞, 2>
AnB=B=<0,2)
A\B=(-∞, 0)
B\A=zbiór pusty

A=<-1,2>
B=<2, +∞)
AuB=<-1,+∞)
AnB={2}
A\B=<-1,2)
B\A=(2,+∞)
Najlepsza Odpowiedź!
2009-10-25T14:09:47+01:00
Wyznacz zbiory AuB, AnB, A/B, B/A

a) A = (-3;0), B= <-1;4)

AuB=(-3,4)
AnB=<-1,0)
A/B=(-3,-1)
B/A=<0,4)

b) A = (-4;2>, B= <-½;3)
AuB=(-4,3)
AnB=<-½,2>
A/B=(-4,-½)
B/A =(2,3)
c) A = (-∞ ; 2>, B = <0;2)
AuB=A
AnB=B
A/B=(-∞,0)
B/A =zbior pusty
d) A = <-1;2>, B = <2; ∞)
AuB=<-1,∞)
AnB={2}
A/B=<-1;2)
B/A =(2; ∞)
2 5 2